Nomogram for Predicting Individual Survival After Recurrence of Advanced-Stage, High-Grade Ovarian Carcinoma. Issue 2 (February 2019) - Rose, Peter G.; Java, James J.; Salani, Ritu; Geller, Melissa A.; Secord, Angeles Alvarez; Tewari, Krishnansu S.; Bender, David P.; Mutch, David G.; Friedlander, Michael L.; Van Le, Linda; Method, Michael W.; Hamilton, Chad A.; et al.
Abstract : OBJECTIVE: To analyze clinical prognostic factors for survival after recurrence of high-grade, advanced-stage ovarian–peritoneal–tubal carcinoma and to develop a nomogram to predict individual survival after recurrence. METHODS: We retrospectively analyzed patients treated in multicenter Gynecologic Oncology Group protocols for stage III and IV ovarian–peritoneal–tubal carcinoma who underwent primary debulking surgery, received chemotherapy with paclitaxel and a platinum compound, and subsequently developed recurrence. Prognostic factors affecting survival were identified and used to develop a nomogram, which was both internally and externally validated. RESULTS: There were 4, 739 patients included in this analysis, of whom, 84% had stage III and 16% had stage IV ovarian carcinoma. At a median follow-up of 88.8 months (95% CI 86.2–92.0 months), the vast majority of patients (89.4%) had died. The median survival after recurrence was 21.4 months (95% CI 20.5–21.9 months). Time to recurrence after initial chemotherapy, clear cell or mucinous histology, performance status, stage IV disease, and age were significant variables used to develop a nomogram for survival after recurrence, which had a concordance index of 0.67. The time to recurrence alone accounted for 85% of the prognostic information. Similar results were found for patients who underwent second look laparotomy and had a complete pathologic response or received intraperitoneal chemotherapy. CONCLUSION: For individuals with advanced-stage ovarian carcinoma who recur after standard first-line therapy, estimated survivals after recurrence are closely related to the time to recurrence after chemotherapy and prognostic variables can be used to predict subsequent survival. CLINICAL TRIAL REGISTRATION: ClinialTrials.gov, NCT00002568, NCT00837993, NCT00002717, NCT01074398, and NCT00011986. Abstract : After advanced-stage ovarian carcinoma recurs, prognostic variables including time to recurrence, patient age, performance status, histology, and stage accurately predict subsequent survival.